Involvement of Tumor Necrosis Factor Receptor Type II in FoxP3 Stability and as a Marker of Treg Cells Specifically Expanded by Anti–Tumor Necrosis Factor Treatments in Rheumatoid Arthritis. Issue 4 (20th February 2020) - Santinon, François; Batignes, Maxime; Mebrek, Majda Lyna; Biton, Jerôme; Clavel, Gaëlle; Hervé, Roxane; Lemeiter, Delphine; Breckler, Magali; Busato, Florence; Tost, Jorg; Ziol, Marianne; Boissier, Marie‐Christophe; et al.
Abstract : Objective: To study the involvement of Treg cells expressing tumor necrosis factor receptor type II (TNFRII) in exerting control of inflammation in experimental models and in the response to anti‐TNF treatments in patients with rheumatoid arthritis (RA) or spondyloarthritis (SpA). Methods: The role of TNFRII in Treg cells was explored using a multilevel translational approach. Treg cell stability was evaluated by analyzing the methylation status of the Foxp3 locus using bisulfite sequencing. Two models of inflammation (imiquimod‐induced skin inflammation and delayed‐type hypersensitivity arthritis [DTHA]) were induced in TNFRII −/− mice, with or without transfer of purified CD4+CD25+ cells from wild‐type (WT) mice. In patients with RA and those with SpA, the evolution of the TNFRII+ Treg cell population before and after targeted treatment was monitored. Results: Foxp3 gene methylation in Treg cells was greater in TNFRII −/− mice than in WT mice (50% versus 36.7%). In cultured Treg cells, TNF enhanced the expression, maintenance, and proliferation of Foxp3 through TNFRII signaling. Imiquimod‐induced skin inflammation and DTHA were aggravated in TNFRII −/− mice ( P < 0.05 for mice with skin inflammation and P < 0.0001 for mice with ankle swelling during DTHA compared to WT mice). Adoptive transfer of WT mouse Treg cells into TNFRII −/− mice prevented aggravation of arthritis. In patients with RA receiving anti‐TNF treatments, but not those receiving tocilizumab, the frequency of TNFRII+ Treg cells was increased at 3 months of treatment compared to baseline (mean ± SEM 65.2 ± 3.1% versus 49.1 ± 5.5%; P < 0.01). In contrast, in anti‐TNF–treated patients with SpA, the frequency of TNFRII+ Treg cells was not modified. Conclusion: TNFRII expression identifies a subset of Treg cells that are characterized by stable expression of Foxp3 via gene hypomethylation, and adoptive transfer of TNFRII‐expressing Treg cells ameliorates inflammation in experimental models. Expansion and activation of TNFRII+ Treg cells may be one of the mechanisms by which anti‐TNF agents control inflammation in RA, but not in SpA.